Paepalanthus echinoides (Eriocaulaceae), a new species from central Brazil with notes on leaf and scape anatomy - Trovó, Marcelo; Silva, Arthur; Coan, Alessandra Ike (Phytotaxa, 2015)
Paepalanthus echinoides, a new species of Paepalanthus sect. Conodiscus, is described and illustrated. This new species is endemic to central Brazil, growing in sandy and humid soils. It is easily distinguished by its dimerous flowers, small leaves arranged in a rosette, the capillaceous and numerous scapes, the small capitula, and the adpressed, dark brown spathes. We present comparisons with P. sphaerocephalus and P. exiguus, the other two species of P. sect. Conodiscus. We also provide a distribution map and photographs, as well as comments on morphological variation, anatomy of leaves and scapes, habitat, phenology, and conservation status.